Methodical approaches to efficient use of alternative refrigerating agents in refrigerating molding composite refrigeration equipment (Transport systems and technologies, 2019)
been established depending on the modes of its operation when using an alternative refrigerant. Analysis of the thermodynamic parameters of an alternative refrigerant in the refrigeration cycle has been carried out using the heat conversion coefficient. Based on the proposed methodology, approaches to the rational choice of an alternative refrigerant for existing refrigeration equipment have been defined. A study has been conducted on the possibility of using clean, rather than mixed, alternative refrigerating agents in the existing equipment of refrigerated wagons..
Keywords: refrigerated rolling stock, refrigerator, alternative refrigerant, quality indicators, efficiency of use